Jack and Jill : a village story - Alcott, Louisa May, 1832-1888.; Ives, Ruth. (Garden City, N. Y. : Nelson Doubleday, Inc., 1956)
When friends Jack and Jill are injured in a sledding accident, their family and friends rally around them to help in their recovery.
Keywords: Family life -- Fiction; Friendship -- Fiction; Winter -- Fiction